Evidence synthesis of Chinese medicine for monkeypox: Suggestions from other contagious pox-like viral diseases - Rong, Hong-guo; Zhang, Xiao-wen; Han, Mei; Sun, Xin; Wu, Xiao-dan; Lai, Xiao-zhen; Shen, Chen; Yu, Wei-jie; Fang, Hai; Fei, Yu-tong; Liu, Jian-ping (Frontiers in Pharmacology, 2023)
Background: Monkeypox, a zoonotic disease caused by an Orthopoxvirus, presents an etiology similar to smallpox in humans. Currently, there are no licensed treatments for human monkeypox, so clear and urgent research on its prophylaxis and treatment is needed. Objective: The purpose of this study was to explore the evidence of Chinese medicine for contagious pox-like viral diseases and provide suggestions for the multi-country outbreak management of monkeypox. Methods: The review was registered on INPLASY (INPLASY202270013). Ancient classics in China and clinical trials involving randomized controlled trials , non-RCTs, and comparative observational studies of CM on the prevention and treatment of monkeypox, smallpox, measles, varicella, and rubella were retrieved from the Chinese Medical Code (fifth edition), Database of China Ancient Medicine, PubMed, the Cochrane Library, China National Knowledge Infrastructure, Chongqing VIP, Wanfang, Google Scholar, International Clinical Trial Registry Platform, and Chinese Clinical Trial Registry until 6 July 2022. Both quantitative and qualitative methods were applied to present the data collected. Results: The use of CM to control contagious pox-like viral diseases was traced back to ancient Chinese practice cited in Huangdi’s Internal Classic, where the pathogen was recorded nearly two thousand years back. There were 85 articles (36 RCTs, eight non-RCTs, one cohort study, and 40 case series) that met the inclusion criteria, of which 39 studies were for measles, 38 for varicella, and eight for rubella. Compared with Western medicine for contagious pox-like viral diseases, CM combined with Western medicine showed significant improvements in fever clearance time (mean difference, −1.42 days; 95% CI, −1.89 to −0.95; 10 RCTs), rash/pox extinction time (MD, −1.71 days; 95% CI, −2.65 to −0.76; six RCTs), and rash/pox scab time (MD, −1.57 days; 95% CI, −1.94 to −1.19; five RCTs). When compared with Western medicine, CM alone could reduce the time of rash/pox extinction and fever clearance. Chinese herbal formulas, including modified Yinqiao powder, modified Xijiao Dihaung decoction, modified Qingjie Toubiao decoction, and modified Shengma Gegen decoction, were frequently applied to treat pox-like viral diseases and also showed significant effects in shortening the time of fever clearance, rash/pox extinction, and rash/pox scabs. Compared with Western medicine (placental globulin) or no intervention, eight non-randomized trials and observational studies on the prevention of contagious pox-like viral diseases showed a significant preventive effect of Leiji powder among high-risk populations. Conclusion: Based on historical records and clinical studies of CM in managing contagious pox-like viral diseases, some botanical drugs could be an alternative approach for treating and preventing human monkeypox. Prospective, rigorous clinical trials are urgently needed to confirm the potential preventive and treatment effect of Chinese herbal formulas. Systematic Review Registration: [https://inplasy.com/], identifier [INPLASY202270013].